2022
DOI: 10.1139/er-2022-0022
|View full text |Cite
|
Sign up to set email alerts
|

The effects of roadways on lakes and ponds: a systematic review and assessment of knowledge gaps

Abstract: As the global population increases, the expansion of road networks has led to the destruction and disturbance of terrestrial and aquatic habitats. Road-related stressors have significant effects on both lotic and lentic habitats. While there are several systematic reviews that evaluate the effects of roads on lotic environments, there are none that consider their effects on lentic habitats only. We conducted a literature review to achieve two objectives: 1) to summarize the effects of roads on the physical, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 186 publications
0
2
0
Order By: Relevance
“…We also predicted that; (iii) populations residing in larger settlements might experience heightened human disturbance due to a larger number of inhabitants and tourists resulting in decreased snake abundance. Additional to the negative effect of urban land cover and human disturbance, we also predicted that; (iv) road density; and (v) the proximity of roads would both negatively influence snake abundance due to road pollutants (Dixon et al 2022;Yang et al 2014) and higher risk of road mortality (Hallisey et al 2022). Moreover, it has been shown previously that the area of road cover and the proximity of roads positively correlate with the fluctuating asymmetry of dice snakes assuming higher developmental instability (Mészáros et al 2023).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…We also predicted that; (iii) populations residing in larger settlements might experience heightened human disturbance due to a larger number of inhabitants and tourists resulting in decreased snake abundance. Additional to the negative effect of urban land cover and human disturbance, we also predicted that; (iv) road density; and (v) the proximity of roads would both negatively influence snake abundance due to road pollutants (Dixon et al 2022;Yang et al 2014) and higher risk of road mortality (Hallisey et al 2022). Moreover, it has been shown previously that the area of road cover and the proximity of roads positively correlate with the fluctuating asymmetry of dice snakes assuming higher developmental instability (Mészáros et al 2023).…”
Section: Introductionmentioning
confidence: 84%
“…This result implies that dice snake populations in areas with a more intense road network and closer to the main roads are more abundant. Earlier research has demonstrated that roads can exert significant biological, physical, and chemical effects on both terrestrial and aquatic ecosystems (Dixon et al 2022), including the introduction of pollutants (Wang et al 2020), habitat fragmentation (Hamer et al 2021), road mortality (Farias et al 2022), and alterations to thermal regimes (Wang et al 2021). The thermal conditions within human settlements undergo substantial changes compared to rural areas due to the substitution of vegetative cover with impermeable, heat-absorbing artificial surfaces like buildings, concrete pavements, parking lots and asphalt roads (Wang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Road surface solids are diverse in composition. In addition to traffic-related activities, air deposition [25] and nearby soil [26] also contribute solids to the environment around urban roads. During transport, complicated mixing mechanisms are used for solids that are deposited on road surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Road development is one of the main drivers of land use and cover change, leading to habitat fragmentation, degradation, and loss of native species (Dixon et al, 2022 ; Moore et al, 2023 ). This anthropogenic drive also increases fauna collision probability, which varies depending on the value of the functional traits related to the species' vulnerability to roadkill (González‐Suárez et al, 2018 ; Rytwinski & Fahrig, 2012 ).…”
Section: Introductionmentioning
confidence: 99%